2003
DOI: 10.1051/0004-6361:20030463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemi-ionization and chemi-recombination processes on the population of hydrogen Rydberg states in atmospheres of late type dwarfs

Abstract: Abstract. We study the influence of a group of chemi-ionization and chemi-recombination processes on the populations of higher states of hydrogen in the layers of a stellar atmosphere. The group of processes includes ionization:, where H * (n) is the hydrogen atom in a state with the principal quantum number n 1, and H + 2 is the hydrogen molecular ion in a weakly bound rho-vibrational state of the ground state. These processes have been treated within the framework of the semi-classical approximation, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…In contrast, for A = He, the excited helium state with n = 3 can be taken as the lower boundary of the block of Rydberg states. This was also used in Mihajlov et al (2003), who focused on the chemi-ionization processes in DB white dwarf atmospheres.…”
Section: Theoretical Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for A = He, the excited helium state with n = 3 can be taken as the lower boundary of the block of Rydberg states. This was also used in Mihajlov et al (2003), who focused on the chemi-ionization processes in DB white dwarf atmospheres.…”
Section: Theoretical Remarksmentioning
confidence: 99%
“…However, since the influence of strong electromagnetic emission is the same in helium-rich atmospheres as in the Sun, the distribution shape of the helium excited-atom population probably deviates considerably from the Boltzmann distribution. Taking this into account and because the data on the relative efficiencies of atom-Rydberg atom processes and the relevant concurrent processes would be useful for future non-LTE stellar-atmosphere models, the chemi-ionization processes in He * (n) + He collisions were studied in Mihajlov et al (2003) in the context of DB white dwarf atmospheres, within the models proposed by Koester (1980). In the current A&A 552, A33 (2013) study, for the same reason and using the same models, the efficiencies of the excitation processes…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained were used as a basis to study the processes (1a)−(2b) in the weakly ionized layers of the Solar atmosphere (Mihajlov et al 1997b) and atmospheres of cool stars (Mihajlov et al 2003b). The efficiency of these processes was compared with the efficiency of the other relevant ionization and recombination processes, namely, with the electron-atom impact ionization, electron-electron-ion recombination, and electronion photo-recombination processes…”
Section: Introductionmentioning
confidence: 99%
“…In the case of hydrogen and helium atoms, the resonant mechanism was used to analyze the chemi-ionization and their inverse chemi-recombination processes [27][28][29][30][31][32][33]. It was shown that in weakly ionized hydrogen and helium plasmas the chemiionization/recombination processes caused by the resonant mechanism can be dominant in populating the Rydberg's states.…”
Section: Introductionmentioning
confidence: 99%